Factors Associated With the Recovery of Left Ventricular Ejection Fraction in Patients With Anthracycline-Induced Left Ventricular Dysfunction - Tyler Shugg PharmD, PhD; Tk Nguyen PharmD; Xuesi Hua BS; Blair Richards MPH; James Rae PhD; Robert Dess MD; Daniel Perry MD; Bradley Kay MD; Salim S. Hayek MD; Monika Leja MD; Jasmine A. Luzum PharmD, PhD (Journal of Cardiovascular Pharmacology and Therapeutics)
Background Neurohormonal blocking drugs, like beta-blockers, angiotensin-converting enzyme inhibitors (ACEIs), and angiotensin receptor blockers (ARBs), are recommended for treating anthracycline-induced left ventricular dysfunction (AILVD). However, there is limited evidence supporting their benefit. Therefore, this study evaluated associations of neurohormonal blockers and other clinical factors with recovery of left ventricular ejection fraction (LVEF) in patients with AILVD. Methods This retrospective chart review assessed patients treated with at least one dose of anthracycline, then had ≥10% LVEF reduction or post-anthracycline LVEF value <50%, and then had a follow-up LVEF measurement ≥90 days later. The primary endpoint was LVEF recovery (highest follow-up LVEF−lowest LVEF post-anthracycline). Variables from univariable tests with P  < .1 were incorporated in a multiple linear regression model for independent factors significantly associated with LVEF recovery ( P  < .05). Results Out of 104 patients, 83% were female, 86% self-reported white race, 53% had breast cancer, median (IQR) age was 52 (22) years, and LVEF recovery was 14% (16%). The final multivariable model included 2 significant variables: beta-blocker dose after anthracycline exposure (every 25 mg increase in beta-blocker dose was associated with 5.0% increase in LVEF recovery; P  = .0005) and the time between the start of the anthracycline and the lowest LVEF post-anthracycline (every 5-year increase in time was associated with 1.8% decrease in LVEF recovery; P  = .0379). Conclusions In patients with AILVD, a higher beta-blocker dose and earlier detection of LVEF reduction post-anthracycline were significantly and independently associated with improved LVEF recovery. These findings need to be validated in a larger, independent cohort.